2015
DOI: 10.1016/j.cmi.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency-associated viral oncogenesis

Abstract: Several viruses with different replication mechanisms contribute to oncogenesis by both direct and indirect mechanisms in immunosuppressed subjects after solid organ transplantation, after allogeneic stem cell transplantation, or with human immunodeficiency virus (HIV) infection. Epstein-Barr virus (EBV), human papillomavirus (HPV), Kaposi sarcoma herpesvirus (KSHV), human T-cell lymphotropic virus type 1 (HTLV-1) and Merkel cell polyoma virus (MCV) are the main viruses associated with the development of cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 93 publications
4
33
0
1
Order By: Relevance
“…Neither treatment nor achievement of SVR resulted in lower rates of nonliver cancers, although HIV infection was an independent risk factor for non‐HCC cancer. This finding is not unexpected; previous studies have shown that HIV raises the risk of several types of cancer with known infectious causes .…”
Section: Discussionsupporting
confidence: 69%
“…Neither treatment nor achievement of SVR resulted in lower rates of nonliver cancers, although HIV infection was an independent risk factor for non‐HCC cancer. This finding is not unexpected; previous studies have shown that HIV raises the risk of several types of cancer with known infectious causes .…”
Section: Discussionsupporting
confidence: 69%
“…EBV also causes severe clinical manifestations in persons with HIV disease, including oral hairy leukoplakia, end-organ inflammation, and lymphoma [33,34]. Previous studies by our group [35,36] have shown a reduction in EBV replication associated with ART use, which was also observed in this study.…”
Section: Discussionsupporting
confidence: 75%
“…The elevated risk could be related to the underlying lung condition in the native lung when only one lung was transplanted, repeated infections, or chronic smoking [31, 32]. The small number of lung transplant recipients, of which only two were diagnosed with cancer, was one of the limitations of our study.…”
Section: Discussionmentioning
confidence: 99%